ANÁLISE DE EPISÓDIOS DE REESCRITA REVELADORES DA CONSTRUÇÃO DE UM ESTILO - Fiad, Raquel Salek (Organon, 2012)
This paper discusses some aspects of the acquisition of written language, withemphasis on the acquisition of style. Based on a indiciary paradigm, some particular aspectsof the construction of written language are presented. The methodology includes thecomparison of different texts with different versions written by the same author.